Agent-based Model and its Potential in Simulating Some Physical Systems. (August 2019) - Viridi, S; Haryanto, F
Abstract: Agent-based model (ABM) is very flexible in defining types of interaction between agents including non-physical ones, which can be used to simulate social interaction, economy, until city development. Only our abstraction in defining the interactions is the limitation. For a physical system, an agent can be considered as a particle and interaction between them is simply the interaction force, e.g. nuclear force between nucleons, electrostatic force between ions, gravitation force between asteroids, and contact force between granular particles. In this work, simple rule for the interaction between particle is proposed and several materials phases such as solid, liquid, gas, and granular can be obtained, but only qualitatively.